Maternal, infant and childhood risks associated with advanced paternal age: The need for comprehensive counseling for men. (July 2019) - Phillips, N.; Taylor, L.; Bachmann, G.
Highlights: Advanced paternal age (APA) is increasing. Pregnancies of men 45 years and over have increased risks of antenatal complications. Infants of fathers of APA have an increased risk for adverse birth outcomes. These offspring have increased psych, neurocognitive disorders, and childhood cancers. Reproductive counseling and sperm banking may be an option in men who are planning to delay fatherhood. Abstract: The increasing maternal age at first birth is well recognized, but much less discussed are the fact that the prevalence of advanced paternal age (APA) is also increasing and the societal implications of this trend. Over the past 40 years in the United States, the proportion of infants born to fathers of APA, which has been variably defined as above 35 or above 45, increased from ˜4% to 10% (Khandwala et al., 2017, 2018) While there has been extensive research regarding infertility and comorbidities in the aging mother, relatively few studies have explored similar reproductive factors in aging men. However, evidence does suggest a decrease in fertility and an increase in pregnancy complications such as gestational diabetes, intrauterine growth restriction and preterm birth. Additionally, the offspring of fathers of APA have increased risks of chromosomal and non-chromosomal birth defects and an increased incidence of childhood autism and cancers. This review explores the data, with the intent that key counseling points, including the suggestion of sperm banking, can be highlighted when advising the midlife and older man who is considering paternity.